Two-Stage Approach for the Assessment of Distributed Generation Capacity Mixture in Active Distribution Networks - Jayaweera, Dilan; Islam, Syed; Neduvelil, S. (American Institute of Physics, 2013)
Distribution networks are limited with spare capacities to integrate increased volumes of distributed generation (DG). Network constraints and congestion, dynamic thermal limits, intermittent outputs, and the need for reduction in greenhouse gas emission increase the complexity of capturing optimal DG mixture that can safely permit the optimal operation. This paper investigates this problem in detail and proposes a two-stage approach for the quantification of optimal DG capacity mixture in an active distribution network. The approach is aimed at operational planning and takes into account dynamic thermal limits, network internal benefit, and network external benefit and then optimizes samples of DG mixtures through sequential simulation. A case study is performed incorporating wind and photovoltaic generation as intermittent DG and diesel units as standing reserve units. Results suggest that specific operating conditions in an active distribution network can dominate the optimal DG mixture. Wind and diesel hybrid operation can be the most beneficial DG mixture compared to any other DG combination. Dynamic thermal limits of assets can potentially control the type of DG of the optimized mixture.